The Use of VideoScribe Training to Improve Professional Competence of MTs EFL teachers in Pinrang - Dwi Wulandari Ramadhanianti; Zulfah Fakhruddin; Ambo Dalle; Abdul Haris Sunubi; Magdahalena Tjalla (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study aims to improve the professional competence of teachers in designing English learning materials through VideoScribe training. This study was action research. The training was given to 5 English teachers at the Madrasah Tsanawiyah level (Islamic junior high school). Data were collected by using rubric, observation, and interviews. The results show that teachers can operate VideoScribe application after receiving learning technology training with training materials including: (1) creating teachers’ account, (2) designing background, (3) adding pictures and setting the time duration, (4) adding text and setting the time duration, (5) operating, copy, cut, paste, (6) adding scribe hands, (7) setting camera and clear element’s camera, (8) adding music or voiceover, and (9) downloading the scribe video. Indicators of the teacher’s professional competence in operating VideoScribe: (1) being able to understand all the features of VideoScribe, and (2) being able to independently, accurately, and speedily operate all the features in VideoScribe application.